2019
DOI: 10.7759/cureus.4368
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Leg Veins for Restless Leg Syndrome: A Retrospective Review

Abstract: Background: Restless leg syndrome (RLS) and chronic venous insufficiency (CVI) share similar circadian timings and epidemiological characteristics. Objective: The objective of the study was to investigate whether treating superficial venous reflux (SVR) improves the RLS severity in patients with CVI and whether there is an association of the RLS severity with the number of refluxed veins. Materials and methods: Patients with RLS and duplex ultrasound-proven SVR were identified from a data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that varicose vein surgery can improve RLS symptoms and DS ( 4 , 5 ). A study conducted by Hayes et al assessed the impact of varicose vein operation on RLS symptoms in 35 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that varicose vein surgery can improve RLS symptoms and DS ( 4 , 5 ). A study conducted by Hayes et al assessed the impact of varicose vein operation on RLS symptoms in 35 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide new data on rates of RLS symptoms in patients with underlying SVR while corroborating the limited studies which have previously identified a similar association. 4,5,17 Furthermore, the high rate of RLS symptoms in those who found to have SVR suggests an association between the two factors. Therefore, in patients presenting with RLS symptoms, we believe SVR should be actively screened for.…”
Section: Discussionmentioning
confidence: 99%
“…These findings, while limited, are consistent with existing literature on RLS and SVR. 4,5,17 Identifying that SVR associated with RLS symptoms is significant as it provides the possibility of more definitive interventions (i.e., venous ablation of the incompetent superficial venous system by methods including but not limited to radiofrequency, chemical, or surgical ablation) as an alternative to medical management alone. Current estimates of medical management for RLS range from $774 to 2,448 annually 14,16 which makes the typical one-time cost of approximately $2,040 for radiofrequency ablation, a potentially low risk, cost-effective option for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Varicose veins has been previously associated with RLS but our study results did not support this notion as the association between RLS and varicose veins based on multiple regression analysis appeared to be non-significant statistically )OR=5.1, 95% CI=0.68-36.92, p=0.11(. 20,[32][33][34] Moreover, 2 of these studies note that an improvement in RLS symptoms often occurs after superficial venous insufficiency is treated surgically. 33,34 According to the RLSSS and based on our linear regression analysis, other predictors of severe RLS include male gender )Coef.=-2.73, 95% CI= Table 6 -Predictors of restless leg syndrome and severe restless leg syndrome among IBD patients according to multiple logistic and linear regression analysis, respectively.…”
Section: Predictors Of Rls and Severe Rls Among Ibdmentioning
confidence: 99%